Mitochondrial Diversity of the East Balkan Swine (Sus scrofa f. domestica) in South-Eastern Bulgaria - Palova Nadezhda (Sciendo, 2019)
The East Balkan Swine (EBS) is the only preserved local swine breed in Bulgaria and one of the few indigenous pig breeds in Europe. The EBS is distributed in the region of Eastern Balkan Mountains and the Strandja Mountain. To reveal the breed’s genetic profile, we analyzed 50 purebred individuals according to mitochondrial DNA (D-loop region, HVR1) and sequence analysis in the Scientific Center of Agriculture (Sredets region) in the country.